What is rock and roll? - O`Connor, Jim (New York : Penguin Workshop, 2017)
Looks at the history of rock music, its different styles, and its impact on a generation.
Juvenile
Keywords: Juvenile stories -- Rock music Literature Biographies Criticism, interpretation, etc -- New York